2021
DOI: 10.1126/sciadv.abb5943
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic inflammation promotes CCL6-dependent metastatic tumor growth

Abstract: Compelling evidence suggests that inflammatory components contribute to cancer development. However, eosinophils, involved in several inflammatory diseases, were not fully explored in cancer metastasis. We show that airway inflammatory eosinophilia and colonic inflammation with eosinophil infiltration are both associated with increased metastasis in mice. Eosinophilia is responsible for increased bone metastasis in eosinophil-enriched Cd3δ-Il-5 transgenic (Il-5 Tg) mice. We also observe increased eosinophils i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“… 9 , 11 , 14 ). CCR1 is widely expressed in various immune cells, and the knockdown of CCR1 has proved effective in suppressing the maturation and migration of immune cells, thus being regarded as an attractive drug target for the treatment of many autoimmune and allergic diseases, such as asthma 15 18 . Structure-based sequence alignment of CCR1 agonists shows high divergences at the N terminus, with the core region exhibiting conserved similarity, indicating that the N terminus of chemokines contributes to different signal transduction properties of CCR1 (Extended Data Fig.…”
Section: Mainmentioning
confidence: 99%
“… 9 , 11 , 14 ). CCR1 is widely expressed in various immune cells, and the knockdown of CCR1 has proved effective in suppressing the maturation and migration of immune cells, thus being regarded as an attractive drug target for the treatment of many autoimmune and allergic diseases, such as asthma 15 18 . Structure-based sequence alignment of CCR1 agonists shows high divergences at the N terminus, with the core region exhibiting conserved similarity, indicating that the N terminus of chemokines contributes to different signal transduction properties of CCR1 (Extended Data Fig.…”
Section: Mainmentioning
confidence: 99%
“…Different histological subtypes of lung cancer could also have different relationships with inflammation (21), which to some extent explained the differences. Recently Li et al (31) found that in the presence of allergic airway inflammation, eosinophils promoted the adverse effect of tumor metastasis. This team also found a link between eosinophils and tumor metastasis by knocking out eosinophils in some of the mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Li et al ( 31 ) found that in the presence of allergic airway inflammation, eosinophils promoted the adverse effect of tumor metastasis. This team also found a link between eosinophils and tumor metastasis by knocking out eosinophils in some of the mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, they secrete CC-chemokine ligand 6 (CCL6) to attract tumor cells to the bone metastatic niche through CC-chemokine receptor 1 (CCR1). Inhibition of the CCL6-CCR1 signaling significantly attenuates the tumor cell migration and bone metastasis formation, which suggests the close connection between inflammation and metastasis and provides new paradigms for cancer prevention ( 25 ). Furthermore, plasmacytoid dentritic cells have been described in mouse models of breast cancer bone metastasis.…”
Section: Immune Cells Modulating Metastatic Niche Formation In the Bonementioning
confidence: 99%